Call to action? Survey highlights the shortcomings of business-as-usual in addressing gender equality in the fishery sector - Williams, Meryl J.; Choo, Poh Sze (Asian Fisheries Society, 2014)
In the fishery sector, too little attention is paid to gender equality, and gender-blind policies and programmes render the issue as peripheral or invisible. Since 1990, the Asian Fisheries Society (AFS) has paid sustained attention to gender, although at a modest level. In order to gauge how the small cadre of gender experts perceived progress in mobilising attention and action on gender in fisheries, we conducted an online structured survey. Using Actor Network Theory as the questionnaire framework, we analysed the responses from 41 experts. The respondents perceived that the understanding of the gender inequality issues has progressed well but the strategic messages arising are not communicated strongly nor well targeted. Few workers, and even fewer full time professionals, are dedicated to the field of gender research and action, and research is not well linked to grassroots needs. Therefore, the field suffers from weak efforts to enroll more champions, leaders and actors and reach critical mass for mobilisation for gender equality. For mobilisation to happen, targeted, dedicated resources are urgently needed, including full time people, institutional support and projects. To achieve this will require strong, perhaps even confrontational, campaigns and plans, from within the fishery sector, led by a self-nominated core group of committed women and men concerned with inequality in the fishery sector.